A produção escolar do gênero artigo de opinião: um espaço de atuação dialógica - Oliveira, Edinalva Soares de Carvalho (2022)
This study aims to investigate the written production of students-authors of the 2nd and 3rd grades of high school in Brazilian public schools, participating in the 6th edition of the Portuguese Language Olympiad, held in 2019. The general objective is to understand how these students present, develop and articulate arguments in the construction of their texts and which discursive-argumentative strategies they resort to during the production process of the opinion article discursive genre, a fundamental instrument for argumentation, refutation and defense of a point of view, in addition to constitute a discursive act responsive to multiple enunciations in social, political and cultural contexts. The present research, specifically, problematizes some categories of analysis, such as intertextuality and interdiscursiveness, postulated in the view of Bakhtin (2003), the repertoire of articulating elements, discursive modalizers and other linguistic resources, as well as the aspects necessary for understanding of the analysis. It also seeks to encompass autonomy in reading and writing, mastering the functioning of language in specific communication situations and the ability to interact with the speeches of others. For that, it is based on the bibliographic documentary methodology, in particular, on studies from a Bakhtinian perspective, and part of the understanding proposed by Bortoni-Ricardo (2008), that the researcher teacher also sets out to produce knowledge about their professional problems in order to improve your practice. The reflective and analytical work of this dissertation, the result of studies in the Masters in Teaching in Basic Education - Postgraduate Program in Teaching in Basic Education of the Center for Teaching and Research Applied to Education at the Federal University of Goiás (CEPAE/UFG), has as Educational Product the website “Opinion article: exist through writing” (www.artigodeopiniaoedinalva.com.br), which conceives writing as a social action in the form of communication, expression and knowledge and was created due to the need to incorporate reflections and practical notions of multimodality, as well as facilitating instant access to various portals, improving pedagogical efficiency and hosting significant content, enabling its updating. Its preparation follows the guidelines of the Common National Curriculum Base (BNCC), which presents the genre, corpus of this study, as a centrality, recommending the field of social action in the context of language practices.